BUTTERFLY SPECIES RICHNESS AND SEASONALITY IN THE ANACARDIUM PLANTATION - J. B. ATLURI,; K. CHINNA RAO,; D. SANDHYA DEEPIKA,; M. BHUPATHIRAYALU, (The Bioscan, 2011)
The composition, relative abundance and seasonal occurrence of butterflies in Anacardium plantation at visakhapatnam district was carried out during Aril 2008- March 2009. During the study period a total of 555 butterflies belonging to 22 genera with 29 species were encountered. Among the 29 species the most dominant species include Junonia lemonias, Catopsilia pyranthe and Euthalia garuda. The flowers of Anacardium occidantale were foraged for nectar by only six species i.e., Castalius rosimon rosimon, Junonia iphita, Neptis hylas, Graphium agamemnon menides, Catopsilia pyranthe, Junonia lemonias. About half of the total butterflies were encountered during monsoon season (July-October). Euthalia garuda was one of the abundant butterflies in the Anacaridum plantation, which is not so common in other habitat types. This may be due to the availability of mating locations and also because Anacardium ocidantale is one of the main larval host plants of Euthalia garuda.